Enhanced Solubility of the Support in an FDM-Based 3D Printed Structure Using Hydrogen Peroxide under Ultrasonication. (19th March 2018) - Park, Seong Je; Lee, Ji Eun; Park, Jean Ho; Lee, Nak Kyu; Lyu, Min-Young; Park, Keun; Koo, Myung Sool; Cho, Sung Hwan; Son, Yong; Park, Suk-Hee
Abstract : Fused deposition modeling (FDM), one of the archetypal 3D printing processes, typically requires support structures matched to printed model parts that principally have undercut or overhung features. Thus, the support removal is an essential postprocessing step after the FDM process. Here, we present an efficient and rapid method to remove the support part of an FDM-manufactured product using the phenomenon of oxidative degradation of hydrogen peroxide. This mechanism was significantly effective on polyvinyl alcohol (PVA), which has been widely used as a support material in the FDM process. Compared to water, hydrogen peroxide provided a two times faster dissolution rate of the PVA material. This could be increased another two times by applying ultrasonication to the solvent. In addition to the rapidness, we confirmed that amount of the support residues removed was enhanced, which was essentially caused by the surface roughness of the FDM-fabricated part. Furthermore, we demonstrated that there was no deterioration with respect to the mechanical properties or shape geometries of the obtained 3D printed parts. Taken together, these results are expected to help enhance the productivity of FDM by reducing the postprocessing time and to allow the removal of complicated and fine support structures, thereby improving the design capability of the FDM technique.